2005
DOI: 10.1128/jb.187.23.7918-7930.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Positive Regulatory Loop Controls Expression of the Locus of Enterocyte Effacement-Encoded Regulators Ler and GrlA

Abstract: The formation of attaching and effacing (A/E) lesions on intestinal epithelial cells is an essential step in the pathogenesis of human enteropathogenic and enterohemorrhagic Escherichia coli and of the mouse pathogen Citrobacter rodentium. The genes required for the development of the A/E phenotype are located within a pathogenicity island known as the locus of enterocyte effacement (LEE). The LEE-encoded transcriptional regulators Ler, an H-NS-like protein, and GrlA, a member of a novel family of transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
179
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(188 citation statements)
references
References 47 publications
6
179
0
3
Order By: Relevance
“…Regulation of the LEE is complex and is influenced by multiple environmental factors that act on several chromosomal genes, which in turn fine-tune LEE expression through LEE-encoded regulators, Ler, GrlA and GrlR (Deng et al, 2004;Spears et al, 2006). Once activated, Ler leads to induction of operons LEE2, LEE3, LEE5 and LEE4 (Barba et al, 2005;Haack et al, 2003). More so, GrlA can stimulate expression of Ler (Deng et al, 2004) as well as of LEE2 and LEE4 independently of Ler (Russell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the LEE is complex and is influenced by multiple environmental factors that act on several chromosomal genes, which in turn fine-tune LEE expression through LEE-encoded regulators, Ler, GrlA and GrlR (Deng et al, 2004;Spears et al, 2006). Once activated, Ler leads to induction of operons LEE2, LEE3, LEE5 and LEE4 (Barba et al, 2005;Haack et al, 2003). More so, GrlA can stimulate expression of Ler (Deng et al, 2004) as well as of LEE2 and LEE4 independently of Ler (Russell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The Ler DNAbinding protein is encoded by the LEE (locus of enterocyte effacement) pathogenicity island of enterohaemorrhagic E. coli (EHEC) and EPEC. It activates the transcription of the major virulence operons in the island at 37 u C by opposing the silencing activity of H-NS (Barba et al, 2005;Bustamante et al, 2001;Haack et al, 2003;Umanski et al, 2002). Ler and H-NS are partial paralogues whose oligomerization domains are highly divergent coiled-coils; there is no evidence that Ler and H-NS form heterodimers.…”
Section: Full-length Truncated and Partial Paralogues And Orthologuementioning
confidence: 99%
“…4). The GrlRA regulators constitute a complicated feedback loop whereby GrlA directly activates ler expression, and GrlR acts posttranslationally to reduce the cellular quantity of the GrlA protein (28,61,64,65). Once expressed, Ler, in turn, acts as an H-NS antisilencer to increase the expression of LEE2, LEE3, LEE4, and LEE5 operons (Fig.…”
Section: Figure 4 Stimulation Of Lee and Non-lee Effector Molecules Rmentioning
confidence: 99%
“…To demonstrate the many inputs controlling ler gene expression, researchers working with both EHEC and enteropathogenic E. coli (EPEC) found that Ler is stimulated in response to environmental signals such as temperature, pH, iron, ammonium, calcium, bicarbonate (50)(51)(52)(53)(54), and quorum-sensing signaling (55,56), as well as the proteins IHF (57), Fis (58), BipA (59), PerC homologs, or Pch (60), GrlRA (61,62), and GadX (63) (Fig. 4).…”
Section: Figure 4 Stimulation Of Lee and Non-lee Effector Molecules Rmentioning
confidence: 99%